The 4MOTHERS trial of the impact of a mobile money-based intervention on maternal and neonatal health outcomes in Madagascar: study protocol of a cluster-randomized hybrid effectiveness-implementation trial - Lacroze, Etienne; Bärnighausen, Till; De Neve, Jan-Walter; Vollmer, Sebastian; Ratsimbazafy, Rolland Marie; Emmrich, Peter Martin Ferdinand; Muller, Nadine; Rajemison, Elsa; Rampanjato, Zavaniarivo; Ratsiambakaina, Diana; Knauss, Samuel; Emmrich, Julius (Trials, 2021)
Mobile money—a service enabling users to receive, store, and send electronic money using mobile phones—has been widely adopted across low- and middle-income economies to pay for a variety of services, including healthcare. However, evidence on its effects on healthcare access and health outcomes are scarce and the possible implications of using mobile money for financing and payment of maternal healthcare services—which generally require large one-time out-of-pocket payments—have not yet been systematically assessed in low-resource settings. The aim of this study is to determine the impact on health outcomes, cost-effectiveness, feasibility, acceptability, and usefulness of mobile phone-based savings and payment service, the Mobile Maternal Health Wallet (MMHW), for skilled healthcare during pregnancy and delivery among women in Madagascar.
Gesehen am 09.02.2022